Grade 3 students at Kebayoran Lama Elementary School 19: Game-Based Model for Throwing and Catching Movements - Regi Ramadhan; Eko Prabowo; Mastri Juniarto (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. The objective of the research is to develop a game-based model for fundamental manipulative movements like throwing and catching. The model can be used in physical education classes in elementary schools to assist teachers in teaching these fundamental movements. The created model is expected to be an effective tool in enhancing the learning process of basic manipulative movements in students. Materials and methods. The ADDIE model was utilized in this research which involved five stages - analysis, design, development, implementation, and evaluation. The research resulted in the development of a validated model for basic manipulative throwing and catching movements. The model underwent revision by basic movement expert lecturers, game experts, and elementary school physical education teachers, resulting in a total of 15 lessons. The data collection process consisted of documentation and observation, while data analysis was carried out descriptively. Results. At SD Negeri 19 Kebayoran Lama, a game-based model has been developed to teach third-grade students the fundamental skills of throwing and catching. The purpose of this research is to enhance the basic manipulative abilities of elementary school students through immersive and interactive gameplay. By utilizing a game-based approach, students are motivated to learn and practice the essential skills of throwing and catching. The game-based model provides a fun and engaging way to teach the students, which can lead to improved learning outcomes. This research seeks to contribute to the development of effective teaching methods that can enhance the learning experience of young students while promoting their physical development. Conclusion. The implementation of basic movement models in physical education is a valuable tool for teachers, particularly in the instruction of basic manipulative movements such as throwing and catching. This study examines a game-based manipulative throwing and catching basic movement model for Grade 3 students at SD Negeri 19 Kebayoran. The aim of this model is to provide students with a comprehensive understanding of manipulative movements, while simultaneously engaging them in a fun and interactive manner. By employing this approach, educators can facilitate the acquisition of essential motor skills, improve hand-eye coordination, and promote physical fitness among students.